Broken Windows Theory-Based Spectator Behavior Scale (BWTSBS): a validity and reliability study - Yavuz Eroglu, Sultan; Eroglu, Erdem; Koc, Mustafa Can; Talaghir, Laurentiu-Gabriel; Iconomescu, Teodora Mihaela (Frontiers in Psychology, 2025)
PurposeThe aim of this study is to develop a scale to measure the spectator behaviors of fans and spectators. For this purpose, the research was conducted in two phases.MethodsThe sample of the study consists of 220 fans aged 18 and over who are interested in different sports branches and support various teams across Turkey. Participants were selected from different geographical regions and socio-economic groups to ensure diversity. Stratified sampling method was used in the study. In this method, fans were first stratified according to the sports they support (e.g., soccer, basketball, volleyball) and random samples were selected from each stratum. In this way, it was ensured that each sport branch was represented and the sample better reflected the population.In the study, Personal Information Form and the Audience Behavior Scale Based on Broken Windows Theory (BWTSBS), which has been validity and reliability study to understand the behaviors of the participants, were used as data collection tools.ResultsIn the analysis of the data obtained within the scope of the study, exploratory factor analysis was used for the construct validity of the scale and confirmatory factor analysis was used to verify the structure obtained as a result of this analysis. In this analysis, the extent to which the theoretically determined factor structure overlaps with the data is examined. The goodness of fit indices reveal how well the model fits the data. The CFA used in the study was based on fit criteria such as χ2/df, CFI, GFI, AGFI, NFI, IFI, TLI, RMSEA and RMR to evaluate the fit of the model.